Essays on financial contracting - Jukka Vauhkonen (Bank of Finland, 2004)
This thesis consists of an introductory chapter and four essays on financial contracting theory.In the first essay, we argue that many adverse selection models of standard one-period loan contracts are not robust to changes in market structure.We argue that debt is not an optimal contract in these models, if there is only one (monopoly) financier instead of a large number of competitive financiers. In the second essay, we examine the welfare effects of allowing banks to hold equity in their borrowing firms.According to the agency cost literature, banks equity stakes in their borrowing firms would seem to alleviate firms asset substitution moral hazard problem associated with debt financing.We argue that this alleged benefit of banks equity holding is small or non-existent when banks are explicitly modelled as active monitors and firms have access also to market finance. In the third essay, we extend the well-known incomplete contracting model of Aghion and Bolton to attempt to explain the empirical observation that the allocation of control rights between entrepreneur and venture capitalist is often contingent in the following way.If the company s performance (eg earnings before taxes and interest) is bad, the venture capital firm obtains full control of the company.If company performance is medium, the entrepreneur retains or obtains more control rights.If company performance is good, the venture capitalist relinquishes most of his control rights. The fourth essay is a short note, in which we show that the main result of the model of Aghion and Bolton concerning optimality properties of contingent control allocations in an incomplete contracting environment holds only if an additional condition is satisfied.
URN:NBN:fi:bof-201408071688
Keywords: 330; financial contracts; security design; capital structure; incomplete contracts